2015
DOI: 10.15517/rbt.v63i4.17252
|View full text |Cite
|
Sign up to set email alerts
|

Biology of Rhizoprionodon lalandii (Elasmobranchii: Carcharhinidae) captured by the artisanal fishery of Margarita Island, Venezuela

Abstract: Biology of Rhizoprionodon lalandii (Elasmobranchii: Carcharhinidae) captured by the artisanal fishery of Isla de Margarita, Venezuela. Rhizoprionodon lalandii is a small shark (< 1.5 m) classified as Data Deficient by IUCN; however, in Venezuelan coastal waters, it represents one of the most captured species, with daily landings in many areas of the country, being an important component of traditional dishes with high demand and with an increased economical value in local markets. Due to the lack of biological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Particularly in Venezuela, elasmobranchs are intensively traded for meat and fins in coastal waters, open oceans (Cervigón, ) and, more recently, in deep waters (Tagliafico, Rago, & Ron, ). Additionally, several studies in the region have demonstrated poor management of elasmobranch fisheries, due to high catches of pregnant females and immature individuals (Tagliafico, Rago, Barany, & Rangel, ; Tagliafico, Rago, Rangel, & Mendoza, ; Tavares & Arocha, ).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly in Venezuela, elasmobranchs are intensively traded for meat and fins in coastal waters, open oceans (Cervigón, ) and, more recently, in deep waters (Tagliafico, Rago, & Ron, ). Additionally, several studies in the region have demonstrated poor management of elasmobranch fisheries, due to high catches of pregnant females and immature individuals (Tagliafico, Rago, Barany, & Rangel, ; Tagliafico, Rago, Rangel, & Mendoza, ; Tavares & Arocha, ).…”
Section: Introductionmentioning
confidence: 99%